Novel TMEM127 Variant Associated to Bilateral Phaeochromocytoma with an Uncommon Clinical Presentation - Antía Fernández-Pombo; José M. Cameselle-Teijeiro; Jose A. Puñal-Rodríguez; Lourdes Loidi; Roberto Peinó-García; Paloma Cabanas-Rodríguez; Miguel Garrido-Pumar; Sandra Baleato-González; Enrique Flores-Ríos; David Araújo-Vilar (Case Reports in Endocrinology)
Phaeochromocytomas and paragangliomas are rare catecholamine-secreting tumours arising from the adrenal medulla or sympathetic paraganglia. It is known that 20–30% of all cases occur as a result of germline variants in several well known genes. The TMEM127 gene was recently identified as a new phaeochromocytoma susceptibility gene. However, until a larger sample of cases is available, the prevalence, genotype-phenotype correlation, and a clear predominant biochemical pattern of TMEM127-related PCC, remain to be defined. We present a woman with the pathogenic variant c.86delG (p.Arg29Leufs∗52) in the TMEM127 gene, which has not been previously reported, associated to a bilateral phaeochromocytoma, with an uncommon initial clinical presentation and a biochemical profile that is distinctly adrenergic. Her two young children carry the same variant and are, at present, disease-free. Physicians should be aware that phaeochromocytoma can manifest in an atypical manner, as with episodic hypotension, mainly if the symptoms have no obvious aetiology and they worsen over time. This case also supports the presence of a predominant adrenaline secreting pattern in TMEM127-positive tumours, as well as the need to consider multigene panel testing in patients with bilateral phaeochromocytomas.